Enantioselective radical conjugate additions driven by a photoactive intramolecular iminium-ion-based EDA complex - Cao, Zhong-Yan (Nat Commun, 2018)
The photochemical activity of electron donor–acceptor (EDA) complexes provides a way to generate radicals under mild conditions. This strategy has found application in chemical synthesis and recently in enantioselective catalysis. Reported methods classically relied on the formation of intermolecular EDA complexes, generated upon aggregation of two suitable reagents. Herein, we further expand the synthetic utility of this strategy demonstrating that an intramolecular EDA complex can trigger a photochemical catalytic enantioselective radical process. This approach enables radical conjugate additions to β-substituted cyclic enones to form quaternary carbon stereocenters with high stereocontrol using visible light irradiation. Crucial for success is the use of an amine catalyst, adorned with a carbazole moiety, which generates, upon condensation with enones, chiral iminium ions that show a broad absorption band in the visible region. This optical property originates from an intramolecular charge transfer π–π interaction between the electron-rich carbazole nucleus and the electron-deficient iminium double bond.